2014
DOI: 10.1016/j.afjem.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of the South African Triage Score (SATS) in an urban teaching hospital, Ghana

Abstract: Introduction Triage is the process of sorting patients based on the level of acuity to ensure the most severely injured and ill patients receive timely care before their condition worsens. The South African Triage Scale (SATS) was developed out of a need for an accurate and objective measure of urgency based on physiological parameters and clinical discriminators that is easily implemented in low resource settings. SATS was introduced in the emergency center (EC) of Komfo Anokye Teaching Hospital (KATH) in Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 7 publications
6
63
0
3
Order By: Relevance
“…Upon arrival at the KATH ED, patients are triaged using the South African Triage Score, a scoring system developed in South Africa and since validated in various resource‐limited settings. This ‘triage score’ is generated based on the patient's mobility, respiratory rate, heart rate, systolic blood pressure, temperature, AVPU (alert/verbal/pain/unresponsive) score and trauma . Patients with more abnormal values for these criteria receive a higher triage score.…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival at the KATH ED, patients are triaged using the South African Triage Score, a scoring system developed in South Africa and since validated in various resource‐limited settings. This ‘triage score’ is generated based on the patient's mobility, respiratory rate, heart rate, systolic blood pressure, temperature, AVPU (alert/verbal/pain/unresponsive) score and trauma . Patients with more abnormal values for these criteria receive a higher triage score.…”
Section: Methodsmentioning
confidence: 99%
“…The most widely studied is the South African Triage Scale (SATS), which has shown acceptable validity and reliability in several settings. [10][11][12][13][14][15][16][17] One Malawian study has demonstrated that training staff in emergency skills, introducing triage and improving patient flow can reduce mortality rates and increase efficiency. 18 Although this data is not definitive, it suggests that implementation of triage systems in RLEs has the potential to improve clinical outcomes as well as ED functioning.…”
Section: Triage In Developing Settingsmentioning
confidence: 99%
“…A number of triage scales have been developed for resource‐limited environments (RLEs). The most widely studied is the South African Triage Scale (SATS), which has shown acceptable validity and reliability in several settings . One Malawian study has demonstrated that training staff in emergency skills, introducing triage and improving patient flow can reduce mortality rates and increase efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that support and validate the use of the SATS were conducted mainly in large secondary-and tertiary-level hospitals situated in either urban or rural parts of South Africa. 1,[11][12][13] These hospitals are often better staffed and equipped than district hospitals. A previous audit on the use of SATS in the National District Hospital in Bloemfontein concluded that the tool was poorly implemented.…”
Section: Introductionmentioning
confidence: 99%